Combating Greenwashing of Construction Products in New Zealand and Australia: A Critical Analysis of Environmental Product Declarations - Moshood, Taofeeq Durojaye; Rotimi, James Olabode Bamidele; Rotimi, Funmilayo Ebun (MDPI AG, 2024)
The construction industry’s increasing environmental impact has led to the widespread adoption of sustainability claims, yet the prevalence of greenwashing—where organizations make misleading environmental claims—threatens genuine sustainable development efforts. Environmental Product Declarations (EPDs) have emerged as a potential solution, particularly in the New Zealand and Australia construction sectors, where recent government climate regulations have accelerated their adoption. However, the effectiveness of EPDs in combating greenwashing and their practical implementation remain understudied. This research addresses this gap through a comprehensive analysis of EPDs in construction, employing a systematic literature review of 82 articles from 2010 to 2024 across major databases. Using ATLAS.ti 9 software, this study makes three key contributions: (1) develops a novel framework for evaluating EPD programs and their effectiveness in preventing greenwashing, (2) establishes a standardized methodology for assessing the completeness and accuracy of life cycle assessment information in EPDs, and (3) provides evidence-based recommendations for improving EPD implementation in the construction industry. The findings reveal critical shortcomings in current EPD practices, including inconsistent assessment methodologies and incomplete life cycle data. This study proposes specific reforms to enhance EPD reliability and transparency, offering practical guidelines for industry stakeholders to verify environmental claims. These contributions advance both the theoretical understanding of environmental certification systems and practical implementation of sustainable construction practices by developing regulatory frameworks.
Keywords: 33 Built Environment and Design; 3302 Building; 12 Responsible Consumption and Production; 12 Built Environment and Design